Computational Simulation of Team Creativity: The Benefit of Member Flow - Zu, Chong; Zeng, Hui; Zhou, Xiang (Frontiers in Psychology, 2019)
This study simulates the team cognition model through NetLogo 6.0.2 to view a dynamic changing of team creativity during knowledge sharing when the team members perform problem-solving tasks. A hypothesis is proposed: (a) when people possess various characteristics, members who own high-level normal knowledge and have high communication frequency are suited to perform problem construction process and members who own high-level creative knowledge and have less communication frequency are suited to perform divergent exploration process; (b) member flow that old-timer is replaced by a new member, can improve the team creativity and keep it more stable. The team cognition model is based on the social network of the team, where members are assigned cognition tasks. Also, the simulation experiments are conducted in 6 conditions and each condition has one situation including “MemberFlow” procedure, and one excluding “MemberFlow” procedure. Each experiment contains 500 repetitive experiments and in each repetition, there are 100 steps of “GO” procedure are performed. The results show that the team creativity is maximal and stable in the condition of hypothesis (a), and member flow can optimize the team creativity.